2015
DOI: 10.5455/gmj-30-161185
|View full text |Cite
|
Sign up to set email alerts
|

The levels of HbA1c in patients with thyroid dysfunction

Abstract: Thyroid hormones increase the hepatic glyconeogenesis, glycogenolysis and the absorption of glucose. Glucose intolerance is common in thyroid dysfunction. HbA1c is the most important determinant of long term glysemic status in diabetic patients. HbA1c is affected from various factors. In this study we evaluated the relation between thyroid function tests and HbA1c in non-diabetic patients with thyroid dysfunction. Non-diabetic 43 patients with hyperthyroidism, 20 patients with hypothyroidism and for control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…24 In the present study a positive linear significant correlation was observed between the serum levels of T3, T4 and HbA1c. These findings are supported with other studies, showing that the level of HbA1c is elevated in hyperthyroidism p. 10,17 This result might be explained by the fact that, thyroid hormones facilitate the glycogenolytic and gluconeogenic effects of epinephrine and glucagon and stimulate hepatic gluconeogenic enzymes (phosphorenol pyruvate carboxykinase) increasing blood glucose level and so does HbA1c. Another explanation of the hyperglycemic effect of thyroid hormones could be their anti-insulin actions in different organs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…24 In the present study a positive linear significant correlation was observed between the serum levels of T3, T4 and HbA1c. These findings are supported with other studies, showing that the level of HbA1c is elevated in hyperthyroidism p. 10,17 This result might be explained by the fact that, thyroid hormones facilitate the glycogenolytic and gluconeogenic effects of epinephrine and glucagon and stimulate hepatic gluconeogenic enzymes (phosphorenol pyruvate carboxykinase) increasing blood glucose level and so does HbA1c. Another explanation of the hyperglycemic effect of thyroid hormones could be their anti-insulin actions in different organs.…”
Section: Discussionsupporting
confidence: 89%
“…12,13 The higher levels of FBS and HbAlc in hyperthyroid group compared to normal controls appeared as changes of carbohydrate metabolism. [14][15][16][17] A significant correlation between TSH and HbA1c serum levels has also been found. 18 Low RBC turnover, with a predominance of older cells are associated with a falsely elevated HbA1c.…”
Section: Introductionmentioning
confidence: 99%
“…Both overt and subclinical hypo- and hyperthyroid dysfunction were found associated with HbA1c level and T2D disease. HbA1c levels were significantly higher in the hyperthyroid group when compared with hypothyroid and euthyroid groups [ 19 ]. In this euthyroid T2D population, we found that HbA1c was negatively correlated with FT3 and positively correlated with FT4 and TSH.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on HbA1c in thyrotoxicosis are not consistent. Two studies reported that HbA1c was higher in hyperthyroid patients compared to euthyroid controls; however, one study had a higher fasting plasma glucose ( 12 ) in hyperthyroid patients, the other showed a trend toward higher mean plasma glucose ( 11 ) in hyperthyroid group. Thus, the higher HbA1c in hyperthyroid patients could be easily attributed to the higher glycemia in the hyperthyroid group of patients.…”
Section: Discussionmentioning
confidence: 95%
“…Hyperthyroidism has the opposite effect of increasing RBC turnover (increase in erythropoiesis accompanied by a shortened RBC survival time) ( 10 ), thereby causing a potential reduction in HbA1c relative to the level of glycemia. There are, however, conflicting reports of high ( 11 , 12 ) and low HbA1c ( 13 ) in hyperthyroidism compared to matched controls. But these studies were cross-sectional in nature.…”
Section: Introductionmentioning
confidence: 99%